Proceedings of the 5th International ICST Conference on Cognitive Radio Oriented Wireless Networks and Communications 2010
DOI: 10.4108/icst.crowncom2010.9181
|View full text |Cite
|
Sign up to set email alerts
|

Blind standard identification with bandwidth shape and GI recognition using USRP platforms and SDR4all tools

Abstract: Abstract-In this paper, focusing on identifying standards blindly, we propose a bandwidth shape sensor and a GI (guard interval) sensor using USRP (Universal Software Radio Peripheral) platforms and SDR4all tools. These sensors are fundamental parts of the so-called Blind Standard Recognition Sensor. The blind standard bandwidth sensor is based on a Radial Basis Function Neuronal Network designed in Matlab. We have presented first experience of using blind standard bandwidth sensor in a previous work. We will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Operated on general-purpose processor, GNU Radio realizes the baseband signal process, including modulation, demodulation and operations relative to waveform of signal [6][7]. In GNU Radio, an object-oriented high level programming language, Python, can be used to program the signal processing flow chart, which is composed of several signal processing modules with specific functions.…”
Section: Gnu Radiomentioning
confidence: 99%
“…Operated on general-purpose processor, GNU Radio realizes the baseband signal process, including modulation, demodulation and operations relative to waveform of signal [6][7]. In GNU Radio, an object-oriented high level programming language, Python, can be used to program the signal processing flow chart, which is composed of several signal processing modules with specific functions.…”
Section: Gnu Radiomentioning
confidence: 99%
“…We first review the reported signal classification schemes for spectrum sensing in literatures. In [2], the authors focus on the classification based on signal's power spectrum density (PSD) shape. The cyclic In [6], a classifier for LTE and WiMax is proposed based on detailed analysis of the cyclostationary features from both CP and pilot sub-carriers.…”
Section: Introductionmentioning
confidence: 99%
“…SDR originally means to implement physical layer functions by programmable software instead of dedicated hardware in the radio communication system [10], [11]. Now its application has been extended to realize full wireless protocol stack for wireless systems [12], [13].…”
mentioning
confidence: 99%